Efficacy and safety of endoscopic interventions using the short double‐balloon endoscope in patients after incomplete colonoscopy. Issue 1 (16th October 2014) - Hotta, Kinichi; Katsuki, Shinichi; Ohata, Ken; Abe, Takashi; Endo, Masaki; Shimatani, Masaaki; Nagaya, Tadanobu; Kusaka, Toshihiro; Matsuda, Tomoki; Uraoka, Toshio; Yamaguchi, Yuichiro; Murakami, Yoshitaka; et al.
<x xml:space="preserve">Abstract</x> Background and Aim We have previously reported excellent cecal intubation rates using a short double‐balloon endoscope in patients with a history of incomplete colonoscopy. However, data on the endoscopic treatment of colorectal tumors using a double‐balloon endoscope are limited. The aim of the present study was to evaluate the efficacy and safety of endoscopic intervention of colorectal tumors using a short double‐balloon endoscope. Methods We analyzed data from a multicenter, prospective study on 110 patients (62 men, median age 66.5 years) who underwent total colonoscopy after incomplete colonoscopy to assess the characteristics of colorectal tumors, endoscopic interventions, and complications. Results In all, 113 colorectal tumors were detected in 55 patients; 109 of the tumors were adenomas (24 advanced adenomas) and two each were intramucosal and advanced cancers. Locations of the lesions were eight in the cecum, 30 in the ascending colon, 18 in the transverse colon, 12 in the descending colon, 34 in the sigmoid colon, five in the rectosigmoid and six in the rectum. Average tumor diameter was 6.8 ± 6.3 mm. Fifty‐nine polypectomies, 22 endoscopic mucosal resections, four hot biopsies, and six cold biopsies were done. All endoscopic interventions were successfully completed and no complications were noted. Two advanced cancers were located in the ascending colon and only a double‐balloon endoscope could reach them to take a biopsy sample. Conclusion Double‐balloon endoscopy is effective and safe for endoscopic intervention of colorectal tumors, irrespective of the location, in patients after incomplete colonoscopy.